2005
DOI: 10.1021/es049256l
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Biotic Ligand Model for Freshwater Green Algae:  Surface-Bound and Internal Copper Are Better Predictors of Toxicity than Free Cu2+-Ion Activity When pH Is Varied

Abstract: The freshwater green microalgae Chlorella sp. and Pseudokirchneriella subcapitata (P. subcapitata) were chronically (48 and 72 h, respectively) exposed to copper at various pH levels, i.e., pH 6-7.5 and pH 5.9-8.5, respectively. Concentrations resulting in 50% inhibition of exponential growth rate (EC50) were determined as dissolved Cu, estimated chemical activity of the free Cu2+ ion (as pCu = - log{Cu2+ activity as molarity}), and as external (surface-bound) Cu and internal Cu in the algal cells. With increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 29 publications
3
82
0
Order By: Relevance
“…Metal toxicity to the cells was time-dependent at higher metal concentrations, which might be attributed to the enhanced intracellular metal concentrations. Previous studies demonstrated that the intracellular metal concentration can be used to predict the metal toxicity to the algal cells [23].…”
Section: Long-term Bioaccumulation Of CD and Zn By Microcystismentioning
confidence: 99%
“…Metal toxicity to the cells was time-dependent at higher metal concentrations, which might be attributed to the enhanced intracellular metal concentrations. Previous studies demonstrated that the intracellular metal concentration can be used to predict the metal toxicity to the algal cells [23].…”
Section: Long-term Bioaccumulation Of CD and Zn By Microcystismentioning
confidence: 99%
“…Metals may associate with some ecosystem components resulting in metal complexes with inorganic or organic materials. Considering the amplitude of possibilities for the metal association in the environment, metals bioavailability may vary with environmental conditions and organisms (Lombardi et al 2002;De Schamphelaere et al 2005;Töpperwien et al 2007). Metals such as cadmium and chromium are often present in industrial wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…Binding of Cu to the biotic ligand, as yet unknown in algae but assumed to be on the plasma membrane [32]. Growth inhibition in microalgae has also been related to intracellular Cu concentration [7,33].…”
Section: And Cu Toxicity Testmentioning
confidence: 99%